Egypt: Impacts of the Ukraine and Global Crisis on Food Systems and Poverty: Updated 2022-08-14 - Abay, Kibrom A.; Abdelradi, Fadi; Breisinger, Clemens; Xinshen Diao; Dorosh, Paul A.; Pauw, Karl; Randriamamonjy, Josee; Raouf, Mariam; Thurlow, James (International Food Policy Research Institute, 2022)
Presentation prepared by Kibrom Abay, Fadi Abdelradi, Clemens Breisinger, Xinshen Diao, Paul Dorosh, Karl Pauw, Josee Randriamamonjy, Mariam Raouf, and James Thurlow, Fadi is with the Cairo University, all others with the International Food Policy Research Institute, Washington, DC. This is part of the Global Crisis Country Series.